Esophageal surface cells in Non-erosive Reflux Disease (NERD): Scanning electron microscopic study - Myint, Yi Yi; Tun, Ye (2011)
Dilated intercellular spaces (DIS) in prickle cell layers are considered as early signs of acid damage to the esophageal epithelium. In order to enter the mucosal intercellular spaces, acid and pepsin have to penetrate the intercellular adhesion sites of the most superficial epithelial cells. The aim of this study is to explore cellular attachments in most superficial esophageal cells of non- erosive (NERD) patients. The study group included 8 (NERD) patients and 5 normal controls. Specimens were routinely processed for SEM. The nature of cellular attachment and intercellular spaces between superficial cells of esophageal mucosa were viewed by SEM. Our results showed that cellular attachments in the superficial cells differ significantly (p value 0.007) among the normal controls and patients with NERD (Chi-Square test, p <0.05 was considered to be statistically significant). Our findings supported the concept of abnormal tissue resistance in pathogenesis of NERD patients.